(untitled) (Международный научный журнал «Инженер», 2026)
The article analyzes the role of composite binders in improving the operational characteristics of highquality concrete. It highlights the impact of materials such as fly ash, slags, and polymers on the quality, strength, and durability of concrete. The potential for improving concrete quality through the application of these technologies in Uzbekistan’s construction industry is also discussed. In practice, CEMI 32.5 N and based on B15, B20 and B30 class concrete are mainly used for building buildings and structures, for the manufacture of prefabricated and monolithic concrete and reinforced concrete objects and structures. As an optimized parameter, the strength of the concrete stored for 28 days under normal conditions was obtained. Zero levels are chosen in such a way that the optimized parameter takes the best values of the consistency. Special attention was paid to the production of new technologies, especially concrete, reinforced concrete and polymer materials. The concrete industry has improved the strength, corrosion resistance and environmental safety of concrete with the help of composite materials, polymers, nanomaterials and other innovative additives.